1982
DOI: 10.1002/jcp.1041100116
|View full text |Cite
|
Sign up to set email alerts
|

Two‐factor requirement for murine megakaryocyte colony formation

Abstract: WEHI-3 cell-conditioned medium with the capacity to stimulate megakaryocyte colony formation was separated by Sephadex G-150 column chromatography. The development of colonies containing megakaryocytes was observed only when mixing experiments were performed. Individual fractions did not support megakaryocyte colony growth. The two factors in WEHI-3 CM required for megakaryocyte colony growth had apparent average molecular weights of 35,000 daltons (megakaryocyte CSF) and 100,000 daltons (megakaryocyte potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(63 citation statements)
references
References 20 publications
2
60
1
Order By: Relevance
“…Short-term assays for granulocyte progenitor cells (CFU-GM) and megakaryocyte progenitor cells (CFU-MK) were performed as previously described (14, 15). Briefly, bone marrow cells were cultured as previously described using conditioned medium from WEHI-3 and mouse lung conditioned medium (16,17). Before plating, the bone marrow cells were generally incubated at 370C for 30-60 min at -5 X 106 cells/ml in McCoy's SA medium containing 10% fetal calf serum (FCS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term assays for granulocyte progenitor cells (CFU-GM) and megakaryocyte progenitor cells (CFU-MK) were performed as previously described (14, 15). Briefly, bone marrow cells were cultured as previously described using conditioned medium from WEHI-3 and mouse lung conditioned medium (16,17). Before plating, the bone marrow cells were generally incubated at 370C for 30-60 min at -5 X 106 cells/ml in McCoy's SA medium containing 10% fetal calf serum (FCS).…”
Section: Methodsmentioning
confidence: 99%
“…Marrow cells were cultured at 30-100 X 104 cells/ml in 35-mm petri dishes (Becton-Dickinson & Co.) in modified McCoy's SA medium containing 10% FCS and 0.25% Bactoagar. After incubation (7 d, 370C, 7% C02, 100% humidity), petri dishes were removed from the incubator, dried, and stained in situ for acetylcholinesterase activity (18). Colonies were counted at a magnification of 40.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of GM-CSF on reticulocyte numbers (17) may depend on erythropoietin, a cofactor that was suppressed in our studies by red cell transfusion. The inconsistent effect of GM-CSF on platelet numbers might also reflect variable amounts ofa second factor, e.g., thrombopoietin (22). The increase in platelet count observed after GM-CSF in the two animals with prolonged pancytopenia and bone marrow hypoplasia support an ability of this factor to augment platelet production.…”
Section: Discussionmentioning
confidence: 92%
“…Williams et al have suggested that separate regulatory molecules influence early and late megakaryocytopoiesis. They demonstrated two regulatory factors, which had on average molecular weight of 35,000 (megakaryocytic colony stimulating factor) and 100,000 (potentiating factor) in WEHI-3 murine megakaryocytic leukemic cell conditioned medium (WEHI-3 CM), and that both activities were necessary for maximal colony development and detection (22). Serum thrombopoietin or thrombopoietic stimulating factor derived from the supernatant of a human embryonic kidney cell line has been considered as a potentiator of late megakaryocytopoiesis (23,24).…”
Section: Discussionmentioning
confidence: 99%